Continuous laryngoscopy quantitates laryngeal behaviour in exercise and recovery. Issue 4 (13th July 2016) - Olin, J. Tod; Clary, Matthew S.; Fan, Elizabeth M.; Johnston, Kristina L.; State, Claire M.; Strand, Matthew; Christopher, Kent L.
Exercise-induced laryngeal obstruction (E-ILO) causes exertional dyspnoea. There is no standardised methodology which characterises laryngeal obstruction in relation to exercise or links laryngeal obstruction and dyspnoea severity. Continuous laryngoscopy during exercise (CLE) may improve diagnostic sensitivity by enabling laryngeal visualisation at peak work capacity in patients with rapidly resolving obstruction. The time course of laryngeal obstruction across exercise and recovery has not been quantitated until this report. Adolescents and young adults referred for CLE were laryngoscopically monitored across rest, maximal cycle ergometry exercise, and recovery. Three reviewers, blinded to time sequencing, rated inspiratory glottic and supraglottic obstruction during 10 windows of 15-s corresponding to rest, 25%, 50%, 75%, 90% and 100% of individual symptom-limited peak work capacity (expressed in Watts), and four consecutive recovery windows. 85 patients were screened and 71 included. Over 96% of time windows were interpretable. Laryngeal obstruction severity reached observed maximal levels at peak work capacity, and rapidly resolved. A spectrum of observed maximal obstruction was measured. CLE provides interpretable data demonstrating laryngeal obstruction in patients with suspected E-ILO that is more severe at peak work capacity than during rest, submaximal exercise, or recovery. Observed maximal obstruction was infrequently severe and rapidly resolved. Maximal laryngeal obstruction occurs at peak work capacity in suspected exercise-induced laryngeal obstruction http://ow.ly/pHER300eiU9